A qualitative analysis of the information science needs of public health researchers in an academic setting. - Hunt, Shanda L.; Bakker, Caitlin J. (Journal of the Medical Library Association, 2018)
Objectives: The University of Minnesota (UMN) Health Sciences Libraries conducted a needs assessment of public health researchers as part of a multi-institutional study led by Ithaka S+R. The aims of the study were to capture the evolving needs, opportunities, and challenges of public health researchers in the current environment and provide actionable recommendations. This paper reports on the data collected at the UMN site. Methods: Participants (n=24) were recruited through convenience sampling. One-on-one interviews, held November 2016 to January 2017, were audio-recorded. Qualitative analyses were conducted using NVivo 11 Pro and were based on the principles of grounded theory. Results: The data revealed that a broad range of skill levels among participants (e.g., literature searching) and areas of misunderstanding (e.g., current publishing landscape, open access options). Overall, data management was an afterthought. Few participants were fully aware of the breadth of librarian knowledge and skill sets, although many did express a desire for further skill development in information science. Conclusions: Libraries can engage more public health researchers by utilizing targeted and individualized marketing regarding services. We can promote open science by educating researchers on publication realities and enhancing our data visualization skills. Libraries might take an institution-wide leadership role on matters of data management and data policy compliance. Finally, as team science emerges as a research priority, we can offer our networking expertise. These support services may reduce the stresses that public health researchers feel in the current research environment.